Kepemimpinan Kepala Sekolah dalam Menerapkan Metode Micro-Habits Coaching untuk Meningkatkan Kinerja Pedagogik Guru (Studi Kasus di SMPN 1 Plered Kabupaten Purwakarta) - Yodi Ahmad Sirojudin; Rezcy Setian Suharno; Okke Rosmaladewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the important role of school principals in improving teachers' pedagogical performance through a sustainable coaching approach. Teachers' pedagogical performance still faces various challenges, such as suboptimal lesson planning, limited reflective practices, and insufficient systematic professional assistance. This study aimed to analyze the principal's leadership in implementing the micro-habits coaching method to improve teachers' pedagogical performance at SMP Negeri 1 Plered, Purwakarta Regency. The study employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation studies. The research informants consisted of the principal, vice principals, teachers, and educational staff involved in the implementation of the coaching program. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that the implementation of the micro-habits coaching method was carried out through structured stages of planning, organizing, implementation, and evaluation. The principal played roles as a coach, facilitator, and instructional leader in encouraging changes in teachers' professional behavior through consistent small habits. The implementation of this method was proven to improve teachers' pedagogical performance, particularly in the aspects of lesson planning, instructional implementation, classroom management, and learning evaluation. This study concludes that principal leadership through the micro-habits coaching method is an effective strategy for improving teachers' pedagogical performance and supporting the development of a sustainable learning culture in schools. Keywords: principal leadership, micro-habits coaching, teachers' pedagogical performance, coaching, teacher professional development.